Healthcare seeking practices and barriers to accessing under-five child health services in urban slums in Malawi: a qualitative study. Issue 1 (December 2016) - Lungu, Edgar; Biesma, Regien; Chirwa, Maureen; Darker, Catherine
Abstract Background Access to child health services is an important determinant of child health. Whereas, child health indicators are generally better in urban than rural areas, some population groups in urban areas, such as children residing in urban slums do not enjoy this urban health advantage. In the context of increasing urbanisation and urban poverty manifesting with proliferation of urban slums, the health of under-five children in slum areas remains a public health imperative in Malawi. This paper explores healthcare-seeking practices for common childhood illnesses focusing on use of biomedical health services and perceived barriers to accessing under-five child health services in urban slums of Lilongwe, Malawi's capital city. Methods Qualitative data from 8 focus group discussions with caregivers and 11 in-depth interviews with key informants conducted from September 2012 to April 2013 were analysed using conventional content analysis. Results Whereas, caregivers sought care from biomedical health providers, late care-seeking also emerged as a major theme and phenomenon. Home management was actively undertaken for childhood illnesses. Various health system barriers: lack of medicines and supplies; long waiting times; late facility opening times; negative attitude of health workers; suboptimal examination of the sick child; long distance to health facility; and cost of healthcare were cited in this qualitative inquiry as critical health system factors affecting healthcare-seeking for child health services. Conclusions Interventions to strengthen the health system's responsiveness to expectations are essential to promote utilisation of child health services among urban slum populations, and ultimately improve child health and survival.